Pengaruh Likuiditas, Ukuran Perusahaan, Leverage dan Jaminan Terhadap Peringkat Obligasi pada Sektor Keuangan - Reza Nurrohman; Risal Ronafah; Alfiatul Maulida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to investigate the impact of Liquidity, Company Size, Leverage, and Collateral on Bond Ratings in the Financial Sector. The study centers on Real Estate and Property companies that are publicly traded on the Indonesia Stock Exchange (IDX) from 2017 to 2021, including a total of 28 enterprises. The sampling method used is nonprobability purposive sampling. The major data source for this study is the secondary data obtained from the financial reports of these firms, as published by the IDX. Data collection entails the systematic process of acquiring, recording, and reviewing secondary data using the documentation technique. Analytical approaches encompass descriptive analysis, classical assumption tests, tests for normalcy, multicollinearity, heteroskedasticity, and Autocorrelation. Additionally, hypothesis testing is conducted by t-tests, F-tests, and determination coefficient analysis. The research findings suggest that Liquidity, Company Size, Leverage, and Collateral exert a substantial impact on Bond Ratings within the Financial Sector.